Evaluación técnico financiera de la eficiencia de una nueva tecnología en bombeo electrosumergible para pozos en Colombia y Ecuador (2019)
The objective of this work is to develop a technical and financial evaluation of the performance and efficiency of a new electric-submersible pump system called REDLift®, by means of its comparison with the standard electric submersible pump systems installed initially in six wells from field A and B, in Colombia and Ecuador respectively. The development of the project begins by describing the main characteristics of the two fields of study, in terms of historical review, location, geological framework and production history in order to understand and know the present deposits, their fluids and their productive life. Subsequently, the generalities of the electrosumergible pumping system are detailed, emphasizing in its components, its types applications, failures and limitations, in order to understand its operation and know the technical parameters that allow the evaluation of its performance. Additionally, the characteristics of the new REDLift® technology are described, showing the improvements it has compared to standard technologies, which will be compared and evaluated in the development of the document.